Analisys of Oxygen Consumption Rate in a Closed Transport System for Koi Fish (Cyprinus carpio) Anesthesia with Extracted Green Betel Leaves (Piper betle L) - Manurung, Yeremias Person; Putriningtias, Andika; Haser, Teuku Fadlon (Fakultas Pertanian Universitas Samudra, 2024)
Koi fish are a type of carp that have very beautiful and tame ornaments. This fish is often considered a variant of the Goldfish, even though it is genetically different. Transporting live fish can be defined as an action of moving fish in a living state from one place to another, with measures taken to ensure the fish's survival remains high until they reach their destination. Closed transportation is carried out by means of transport that is not directly connected to the air, often done to maintain the rate of oxygen consumption. Plants called betel leaves serve as herbal medicines and anesthetics for various fish species, including koi fish. This study aims to determine the best dose of green betel leaf extract as an anesthetic for closed transport on the survival of koi fish fry transported for 8 hours, using different doses of 10ml/L, 20ml/L, 30ml/L, and 40ml/L with a Completely Randomized Design (CRD) method. The results of this study show survival rates at doses of 10ml/L 83%, 20ml/L 90%, 30ml/L 77%, and 40ml/L 60%. In addition to testing for survival during transport, this study also aims to measure the Oxygen Consumption Rate (OCR) of each treatment. The results of this study show the OCR test results: P1 0.036 mgO2/min, P2 0.027 mgO2/min, P3 0.025 mgO2/min, and P4 0.022 mgO2/min